Efektivitas Aplikasi Tumbuh Kembang Balita Usia 9–60 bulan - Nilatul Izah; Muhaamad Bakhar; Umi Baroroh (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2019)
Early detection of growth and development is an activity or examination to find early growth and development deviations to make it easier to do further handling or intervention. The method of stimulation carried out so far still relies on health workers being conducted once a month at the posyandu. Previous researchers have made